593 Colonic Perforation Following Major Burns: A Systematic Review. (12th October 2021) - Fadel, M; Iskandarani, M; Cuddihy, J; Jones, I; Collins, D; Kontovounisios, C
Abstract: Introduction: Major burns complicated by stress ulceration and perforation of the stomach or duodenum is a recognised clinical phenomenon. Colonic perforation in burns patients is seemingly uncommon, and the overall incidence, clinical signs/diagnosis of perforation, intervention required, and mortality is incompletely described in the literature. Method: We performed a systematic review of the literature on severe burns resulting in colonic perforation during admission. Relevant studies from January 1975 to June 2020 were retrieved from MEDLINE and EMBASE databases. Patient demographics, total body surface area (TBSA), site of colonic perforation, management and overall outcome were extracted. We present a case series of five major burns patients who had colonic perforations in our Specialist Burns Centre. Results: We identified 54 studies, of which nine (two case series and seven case reports) met the inclusion criteria. In most cases, the TBSA associated with a colonic perforation was ≥ 30% (10/16 patients, 63%) and the abdomen was involved in 9/16 patients (56%). Perforations mainly affected the right colon (12/16 patients, 75%), usually occurring after the second week of admission (13/16 patients, 81%). Right-sided colonic perforations were associated with an increased mortality rate compared to left-sided perforations (42% vs 25%). Conclusions: The current literature, mainly limited to case series and case reports, confirms that colonic perforations in burns patients are rare. The resulting perforation is related to the systemic effect of burn injuries including sepsis and gastrointestinal stasis. We have identified patients who are at higher risk of developing colonic perforations in order to prompt early diagnosis and intervention.